1998
DOI: 10.1017/s0950268898001502
|View full text |Cite
|
Sign up to set email alerts
|

Sustained reduction in the carriage of Neisseria meningitidis as a result of a community meningococcal disease control programme

Abstract: The effect of a community intervention programme of antibiotics and meningitis vaccine on pharyngeal carriage of Neisseria meningitidis was investigated. Carriage rates were determined in pupils at both secondary schools (ages 11-18 years) included in the community intervention programme and compared with two schools outside the area matched for socio-economic status. A total of 1869 pupils were studied 6 months after the programmes, and 2457 pupils after 11 months. Six months after the programme was completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…The decrease in carriers observed among the 10-14 and 15-19 age groups is similar to that observed by Neal et al (1998), yet in this latter study subjects received chemoprophylaxis in addition to vaccine, a factor which could be expected to exert an effect on the reduction in carriers. The slight rise in prevalence observed in the 5-9-year-olds could, in part, be explained by the attenuated effect that polysaccharide vaccine has among the youngest age groups.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The decrease in carriers observed among the 10-14 and 15-19 age groups is similar to that observed by Neal et al (1998), yet in this latter study subjects received chemoprophylaxis in addition to vaccine, a factor which could be expected to exert an effect on the reduction in carriers. The slight rise in prevalence observed in the 5-9-year-olds could, in part, be explained by the attenuated effect that polysaccharide vaccine has among the youngest age groups.…”
Section: Discussionsupporting
confidence: 84%
“…Although other N. meningitidis C carrier studies have also reported a decline in carriage rates, over different periods of time, following vaccination with polysaccharide vaccine (Gotschlich et al, 1969;Stroffolini et al, 1990;Di Martino et al, 1990;Neal et al, 1998), we nevertheless feel that the high number of specimens analysed renders the data yielded by our study of considerable interest.…”
Section: Discussionmentioning
confidence: 51%
“…Whereas carriage rates of serogroup C meningococci are significantly lower than for serogroup B or non-groupable meningococci, and typically less than 1% even in outbreaks, 12 14 17 our study found serogroup carriage rates of 3% by December. This level increases the risk of outbreaks.…”
Section: Discussioncontrasting
confidence: 60%
“…The first was an improvement in swabbing techniques over the first week of the study. Although we were unable to identify the person who took each swab, most were taken by one person (KRN) with considerable experience 12. KRN also supervised the technique of the other operators.…”
Section: Discussionmentioning
confidence: 99%
“…2006) and seven were cross‐sectional surveys carried out post‐vaccination (Hassan‐King et al. 1988; Neal et al. 1998; Smith et al.…”
Section: Resultsmentioning
confidence: 99%